Measurement of Jupiter’s asymmetric gravity field - Iess, L.; Folkner, W. M.; Durante, D.; Parisi, M.; Kaspi, Y.; Galanti, E.; Guillot, T.; Hubbard, W. B.; Stevenson, D. J.; Anderson, J. D.; Buccino, D. R.; Casajus, L. Gomez; et al. (Nature (London), 2018)
Precise Doppler tracking of the Juno spacecraft in its polar orbit around Jupiter is used to determine the planet’s gravity harmonics, showing north–south asymmetry caused by atmospheric and interior flows. Probing the depths of Jupiter The Juno mission set out to probe the hidden properties of Jupiter, such as its gravitational field, the depth of its atmospheric jets and its composition beneath the clouds. A collection of papers in this week's issue report some of the mission's key findings. Jupiter's gravitational field varies from pole to pole, but the cause of this asymmetry is unknown. Rotating planets that are squashed at the poles like Jupiter can have a gravity field that is characterized by a solid-body component, plus components that arise from motions in the atmosphere. Luciano Iess and colleagues use Juno's Doppler tracking data to determine Jupiter's gravity harmonics. They find that the north–south asymmetry arises from atmospheric and interior wind flows. To determine the depths of these flows, Yohai Kaspi and colleagues analyse the odd gravitational harmonics and find that the J 3 , J 5 , J 7 and J 9 harmonics are consistent with the jets extending deep into the atmosphere, perhaps as far as 3,000 kilometres. They conclude that the mass of Jupiter's dynamical atmosphere is about one per cent of Jupiter's total mass. The composition of Jupiter beneath its turbulent atmosphere remains a mystery. If different parts of a spinning object rotate at different rates, then the object probably has a fluid composition. Tristan Guillot and colleagues study the even gravitational harmonics and find that, below a depth of about 3,000 kilometres, Jupiter is rotating almost as a solid body. The atmospheric zonal flows extend downwards by more than 2,000 kilometres, but not beyond 3,500 kilometres, as is also the case with the jets. The gravity harmonics of a fluid, rotating planet can be decomposed into static components arising from solid-body rotation and dynamic components arising from flows. In the absence of internal dynamics, the gravity field is axially and hemispherically symmetric and is dominated by even zonal gravity harmonics J 2 n that are approximately proportional to q n , where q is the ratio between centrifugal acceleration and gravity at the planet’s equator 1 . Any asymmetry in the gravity field is attributed to differential rotation and deep atmospheric flows. The odd harmonics, J 3 , J 5 , J 7 , J 9 and higher, are a measure of the depth of the winds in the different zones of the atmosphere 2 , 3 . Here we report measurements of Jupiter’s gravity harmonics (both even and odd) through precise Doppler tracking of the Juno spacecraft in its polar orbit around Jupiter. We find a north–south asymmetry, which is a signature of atmospheric and interior flows. Analysis of the harmonics, described in two accompanying papers 4 , 5 , provides the vertical profile of the winds and precise constraints for the depth of Jupiter’s dynamical atmosphere.